'Slippery slope' or 'uphill struggle'? Broadening out expert scenarios of climate engineering research and development. Issue 83 (May 2018) - Bellamy, Rob; Healey, Peter
Highlights: Delivering on the Paris Agreement may not be possible without climate engineering ideas. A scenario method explores how far these ideas may develop and under what governance. Scenarios for four climate engineering ideas – BECCS, DACS, SAI and MCB – are developed. We suggest that the governance challenge is less a 'slippery slope' than an 'uphill struggle'. A global carbon price and government investment are incentives with broad applications. Abstract: It is increasingly recognised that meeting the obligations set out in the Paris Agreement on climate change will not be physically possible without deploying large-scale techniques for either removing greenhouse gases already in the atmosphere or reflecting sunlight away from the Earth. In this article we report on the findings of a scenarios method designed to interrogate how far these 'climate engineering' ideas may develop in the future and under what governance arrangements. Unlike previous studies in climate engineering foresight that have narrowly focussed on academic perspectives, a single climate engineering idea and a restricted range of issues, our approach sought to respond to theoretical imperatives for 'broadening out' and 'opening up' research methods applied to highly uncertain and ambiguous topics. We convened a one-day event with experts in climate change and climate engineering from across the sectors of government, industry, civil society and academia in the UK, with additional experts from Brazil, Germany and India. The participants were invited to develop scenarios for four climate engineering ideas: bioenergy with carbon capture and storage, direct air capture and storage, stratospheric aerosol injection and marine cloud brightening. Manifold challenges for future research were identified, placing the scenarios in sharp contrast with early portrayals of climate engineering research as threatening a 'slippery slope' of possible entrenchments, lock-ins and path dependencies that would inexorably lead to deployment. We suggest that the governance challenges for climate engineering should therefore today be thought of as less of a slippery slope than an 'uphill struggle' and that there is an increasingly apparent need for governance that responsibly incentivises, rather than constrains, research. We find that affecting market processes by introducing an effective global carbon price and direct government expenditure on research and development are incentives with broad potential applications to climate engineering. Responsibly incentivising research will involve a pluralistic architecture of governance arrangements and policy instruments that attends to collective ambitions as well as national differences and emerges from an inclusive and reflexive process.